There exist function f ( x ) such that ∀ x ∈ R , the property follows:
A . f ( sin 2 x ) = sin x
B . f ( sin 2 x ) = x 2 + x
C . f ( x 2 + 1 ) = ∣ x + 1 ∣
D . f ( x 2 + 2 x ) = ∣ x + 1 ∣
Have a look at my problem set: SAT 1000 problems
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice approach! Can you prove that the other choices cannot be true?
A function has the property that an input cannot have more than one output.
Option A cannot be correct because I am able to find an input to f ( sin 2 x ) that has two different outputs. If x = 0 then f ( 0 ) = 0 but if x = π / 2 then f ( 0 ) = 1 .
Option B cannot be correct for the same reason that Option A is incorrect. If x = 0 then f ( 0 ) = 0 but if x = π / 2 then f ( 0 ) = π 2 / 4 + π / 2 .
Option C also violates the function property. If x = 1 then f ( 2 ) = 2 but if x = -1 then f ( 2 ) = 0 .
By the process of elimination, we can conclude that Option D is the correct answer. We can think of ∣ x + 1 ∣ as the horizontal deviation from the line x = -1 which happens to be the vertical line separating x 2 + 2 x into two halves. The function f ( x 2 + 2 x ) = ∣ x + 1 ∣ therefore represents the horizontal deviation from the center of the quadratic y = x^{2} + 2x given its y-value (i.e: f(3) = 2 since the point (1, 3) is a difference of 2 units between x = -1 and x = 1). Since the y-values are symmetric across the line x = -1 and each point on y = x^{2} + 2x has the same horizontal deviation from x = -1 as the point symmetric to it, there does not exist any input to the function with more than one output.
Problem Loading...
Note Loading...
Set Loading...
Take f ( x ) = ∣ x + 1 ∣ .
Solution to this problem :
The position coordinates of A , B , F , P , Q , M as ( 2 y 1 2 , y 1 ) , ( 2 y 2 2 , y 2 ) , ( 2 1 , 0 ) , ( − 2 1 , y 1 ) , ( − 2 1 , y 2 ) , ( 4 y 1 2 + y 2 2 , 2 y 1 + y 2 ) .
The condition imposed over the triangle areas yield y 1 y 2 = − 2 .
So we can write x M = 4 y 1 2 + y 2 2 , y M = 2 y 1 + y 2
⟹ 4 y M 2 = 4 x M − 4 ⟹ x M = 1 + y M 2
At y M = 5 0 , x M = 2 5 0 1 .